A Critical Review Of Clinical Application Of Paschimottan Asana - Sharma, M Anand; Sharma, Deepika (International Research Journal of Ayurveda & Yoga, 2021)
Yoga is essentially a spiritual discipline based on an extremely subtle science which Focuses on bringing harmony between mind and body. In yoga sutras Acharya Patanjali defines asana as to be seated in a position that is firm but relaxed, as Paschimottanasana is particularly relevant to Increase the flexibility of vertebral column. Using different research database with the key word Paschimottanasana a comprehensive search of the research literature from core scientific. These studies were integrated in this review. Paschimottanasana searched through ancient literature and yoga literature fulfilled the aim of this article establishing the versatile effect of the Paschimottanasana on the flexibility of vertebral column.